Demon Copperhead : [large type] a novel - Kingsolver, Barbara (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
Southern Appalachia. He was born to a teenaged single mother in a single-wide trailer, with no assets beyond his dead father's good looks and copper-colored hair, a caustic wit, and a fierce talent for survival. Damon braves the perils of foster care, child labor, derelict schools, athletic success, addiction, disastrous loves, and crushing losses. Through all of it, he reckons with his own invisibility in a popular culture where even the superheroes have abandoned rural people in favor of cities.